2019
DOI: 10.1101/584698
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Heparan sulfates are critical regulators of the inhibitory megakaryocyte-platelet receptor G6b-B

Abstract: The immunoreceptor tyrosine-based inhibition motif (ITIM)-containing receptor G6b-B is critical for platelet production and activation, loss of which results in severe macrothrombocytopenia and aberrant platelet function in mice and humans. Using a combination of immunohistochemistry, affinity chromatography and proteomics, we identified the extracellular matrix heparan sulfate (HS) proteoglycan perlecan as a G6b-B binding partner. Subsequent in vitro biochemical studies and a cell-based genetic screen demonst… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…53 Recent reports have demonstrated that HS chains have an unexpected role as regulators of the platelet receptor G6b-B, which functions to attenuate platelet activation and play key roles in platelet production. 54 Interestingly, overexpression of HPSE in mice promotes megakaryopoiesis, 55 and it is plausible that increased HPSE expression by megakaryocytes could play a direct role in generation of hyperreactive platelets. Apart from the contribution of serglycin to alpha-granule development, PGs remain understudied in the context of platelets and it is plausible that G6b-B interactions with HSPGs at the platelet surface function to restrain inappropriate platelet activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…53 Recent reports have demonstrated that HS chains have an unexpected role as regulators of the platelet receptor G6b-B, which functions to attenuate platelet activation and play key roles in platelet production. 54 Interestingly, overexpression of HPSE in mice promotes megakaryopoiesis, 55 and it is plausible that increased HPSE expression by megakaryocytes could play a direct role in generation of hyperreactive platelets. Apart from the contribution of serglycin to alpha-granule development, PGs remain understudied in the context of platelets and it is plausible that G6b-B interactions with HSPGs at the platelet surface function to restrain inappropriate platelet activation.…”
Section: Discussionmentioning
confidence: 99%
“…Unbiased proteomic analysis of vascular surface molecules altered during the course of murine sepsis indicate that platelet degranulation and extracellular matrix remodeling are the top pair of proteomic changes observed in the vasculature 53 . Recent reports have demonstrated that HS chains have an unexpected role as regulators of the platelet receptor G6b‐B, which functions to attenuate platelet activation and play key roles in platelet production 54 . Interestingly, overexpression of HPSE in mice promotes megakaryopoiesis, 55 and it is plausible that increased HPSE expression by megakaryocytes could play a direct role in generation of hyperreactive platelets.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory immunoreceptor tyrosine‐based inhibition motif (ITIM)‐containing receptor G6b‐B binds the heparan sulfate side‐chains of perlecan in the blood vessel wall and plays a central role in maintaining MKs and platelets in a resting state. ( 5,6 ) Mice and humans with null and loss‐of‐function mutations in the gene coding G6b‐B, namely Mpig6b and MPIG6B , respectively, develop a complex MK and platelet phenotype, characterized by severe macrothrombocytopenia, large clusters of MKs and MK fragments in the bone marrow, extramedullary hematopoiesis, and primary focal MF in the marrow and spleen. ( 5,7,8 ) Whether bone health is affected by the G6b‐B deficiency is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Structural models of the receptor bridging complexes were constructed using a combination of AlphaFold2-generated structural models, the crystal structure of the G6b-B ectodomain bound to the 17.4 antibody (9), and manual modelling in ChimeraX (19). AlphaFold2 (20) was used to generate structural models of full-length receptors platelet glycoprotein VI (Uniprot Q9HCN6), G6b-B (Uniprot O95866) and FcgRIIA (Uniprot P31995), using the colab web interface (https://colab.research.google.com/github/sokrypton/ColabFold/blob/main/AlphaFold2.ipynb).…”
Section: Structural Modelingmentioning
confidence: 99%